Lack of collagen XVIII leads to lipodystrophy and perturbs hepatic glucose and lipid homeostasis. (15th June 2020) - Petäistö, Tiina; Vicente, David; Mäkelä, Kari A.; Finnilä, Mikko A.; Miinalainen, Ilkka; Koivunen, Jarkko; Izzi, Valerio; Aikio, Mari; Karppinen, Sanna‐Maria; Devarajan, Raman; Thevenot, Jerome; Herzig, Karl‐Heinz; et al.
Abstract : Key points: Extracellular matrix is highly remodelled in obesity and associates with the development of metabolic disorders, such as insulin resistance. Previously, we have shown that the lack of specific collagen XVIII isoforms impairs adipocyte differentiation in mice. Here, we show that mice lacking the medium and long isoforms of collagen XVIII develop insulin resistance and glucose intolerance and show elevated serum triglycerides and fat accumulation in the liver. We report that collagen XVIII‐deficient mice have increased heat production at low temperatures. These results reveal a new role for collagen XVIII in the regulation of glucose and lipid metabolism, and they expand the understanding of the development of metabolic disorders. Abstract: Liver and adipose tissues play important roles in the regulation of systemic glucose and lipid metabolism. Extracellular matrix synthesis and remodelling are significantly altered in these tissues in obesity and type 2 diabetes. Collagen XVIII is a ubiquitous extracellular matrix component, and it occurs in three isoforms which differ in terms of molecular size, domain structure and tissue distribution. We recently showed that, in mice, the lack of collagen XVIII, and especially its medium and long isoforms, leads to reduced adiposity and dyslipidaemia. To address the metabolic consequences of these intriguing observations, we assessed whole‐body glucose homeostasis in mice challenged with a high‐fat diet and in normal physiological conditions. We observed that, in the high caloric diet, the overall adiposity was decreased by 30%, serum triglyceride values were threefold higher and the steatotic area in liver was twofold larger in collagen XVIII knockout mice compared with controls. We demonstrated that mice lacking either all three collagen XVIII isoforms, or specifically, the medium and long isoforms develop insulin resistance and glucose intolerance. Furthermore, we found that ablation of collagen XVIII leads to increased heat production in low temperatures and to reduction of the high blood triglyceride levels of the knockout mice to the level of wild‐type mice. Our data indicate that collagen XVIII plays a role in the regulation of glucose tolerance, insulin sensitivity and lipid homeostasis, principally through its ability to regulate the expansion of the adipose tissue. These findings advance the understanding of metabolic disorders. Key points: Extracellular matrix is highly remodelled in obesity and associates with the development of metabolic disorders, such as insulin resistance. Previously, we have shown that the lack of specific collagen XVIII isoforms impairs adipocyte differentiation in mice. Here, we show that mice lacking the medium and long isoforms of collagen XVIII develop insulin resistance and glucose intolerance and show elevated serum triglycerides and fat accumulation in the liver. We report that collagen XVIII‐deficient mice have increased heat production at low temperatures. These results reveal a new role for collagen XVIII in the regulation of glucose and lipid metabolism, and they expand the understanding of the development of metabolic disorders.